PENGARUH KUALITAS PELAYANAN PAJAK,PENERAPAN E-FILLING DAN E-BILLINGTERHADAP KEPUASAN WAJIB PAJAK: KEPUASAN WAJIB PAJAK - Wahdini (Yayasan Kayyis Mulia Jaya, 2024)
This research aims to scientifically test and prove the influence of Tax Service Quality, Implementation of e-filling and Implementation of E-billing on Individual Taxpayer Satisfaction in case studies of taxpayers registered at KPP Pratama Pondok Ranji. This type of research uses in-depth quantitative research in the form of numbers. The population in this research is individual taxpayers at KPP Pratama Pondok Aren. The sample in the research was determined based on the simple random sampling method. The number of respondents sampled in this research was 100 respondents. Data were collected using a questionnaire and analyzed using multiple regression using the SPSS version 27 program. The analytical method used was data analysis techniques in the form of data quality testing, classical assumption testing, hypothesis testing and descriptive statistical analysis. The results of the research show that the influence of Tax Service Quality, Implementation of e-filling and Implementation of E-billing has a significant and significant impact on Taxpayer Satisfaction. This shows how important these independent factors are in increasing taxpayer study satisfaction in the case of taxpayers registered at KPP Pratama Pondok Aren. Keywords: influence of tax service quality, implementation of e-filling and implementation of e-billing on individual taxpayer satisfaction.